Plan de acción comunitaria para la comunidad de Lagartococha Distrito del Napo Provincia de Maynas Departamento de Loreto - Guevara Vela, Norith Mery (2024)
The main objective of this work was the development and implementation of a Community Action Plan for the community of Lagartococha, located in the Napo district within the province of Maynas. For which information on the social, cultural and demographic aspects of the town was recorded. Therefore, in sum, the town has 342 residents belonging to the Kichwa indigenous people, where the male population is higher than the female population. In terms of population, Lagartococha represents a young town since the majority of its inhabitants are between 0 and 17 years old. Due to the area in which it is located and the remoteness that this entails, the community lacks basic services. To implement the study and in accordance with the guidelines of the plan, we worked with 34 families who freely and voluntarily signed their acceptance of the project. A Representative Organism of the Executing Nucleus – ORNE was formed, which was made up of 4 members of the community elected in an assembly. The map of actors and the community risk map were prepared in order to understand the dynamics of the different groups that act within the community. The roadmap was established for the adequate attention to queries, complaints and claims. According to the limitations found in the locality, programs were established to strengthen the capacities of both the representative organism of the Executing Nucleus - ORNE and the beneficiary population, which consist of 13 learning workshops. Finally, the campaign called sustainable income is implemented, which considers local purchases, as well as the hiring of local personnel as unskilled labor.